Geology And Exploration Of The Kelsey Lake Diamondiferous Kimberlites, Colorado - Howard G. Coopersmith (Society for Mining, Metallurgy & Exploration, 1991)
A resource of low grade good quality diamonds has been discovered through the Diamond Company NL-Moonstone Diamond Corp. Joint Venture. A limited bulk sample diamond test of two large kimberlite pipes on the Kelsey Lake Property, Colorado, has been completed. These kimberlite pipes have petrological and mineralogical indications of the presence of diamond. Small diamonds were recovered from surface samples. Drilling and trenching revealed both pipes were complexes of diatreme facies kimberlite. One pipe contains crater facies kimberlite as well. This is the first reported occurrence of crater facies kimberlite in the Province. Approximately 1000 tonnes of kimberlite rock was excavated and processed through a scrubber -HMS -Sortex -Grease Plant. Significant diamonds were recovered. The diamonds were generally of good color and clarity, with many being in the gem and near gem categories. Grades are considered low however. Additionally, a small potential resource of alluvial diamonds is present.